Exploding Head Syndrome Accompanied by Repeating Panic Attacks: A Case Report - Kaneko, Yoshiyuki; Kawae, Akiomi; Saitoh, Kaori; Gon, Yasuhiro; Uchiyama, Makoto; Suzuki, Masahiro (Frontiers in Psychiatry, 2021)
To the best of our knowledge, we report here for the first time a case of exploding head syndrome (EHS) that caused repeating panic attacks. A 62-year-old woman experienced a sudden sensation of a loud noise just before going to sleep. The frequency of these episodes rapidly increased to multiple times per night, and she soon began to fear sleep, which led to the occurrence of nighttime panic attacks. She was diagnosed with EHS at our sleep clinic, and clonazepam was prescribed accompanied by reassurance about the benign nature of this syndrome. The intensity of the loud noise gradually reduced, and her fear of sleep and panic attacks disappeared at around the same time. In this report, we argue the importance of gaining further knowledge about EHS, including that about complicating psychiatric symptoms and that about its treatment.